Answer:
Okay, there are many ways to find if a triangle is congruent.
Let's start with some different terminology.
For the sake of simplicity let us say that S stands for when a side is congruent for both triangles and A stands for when an angle (<) is congruent between both the triangles as well.
So, you need to memorize some rules. If you find that 2 triangles are congruent in the sense of; SSS, SAS, AAS, SAA, and ASA. One thing to remember is that Angle Side Side isn't congruent and is called <em>Donkey Theorem</em>. This theorem only works for right triangles.
One way to know if your triangle isn't congruent is if you can find a part of the triangle that is different.
I know that wasn't the best explanation but I hope it helped anyhow. :)
Answer:
B
Step-by-step explanation:
This is how I am confirming the answer:
14/125 = 0.112
125(0.112) = 14
(7^0)^x = 1
7 power zero is 1.
(1^x) = 1
So x can be any value.
x could be, -2, -3, 1, 0, 3, 5, 1.8, -1.5,
x could be any number positive or negative or even zero.
Let's call Frank's house F, Derek's one D n Evan's E.
F(5,-4)
E(-3,-4)
D(-3,4)
FE=5-(-3)=5+3=8
ED=4-(-4)=4+4=8
We can see the triangle is a half of a square, so FD is 8(√2)≈11.312
11.312+8=19.312
The answer is C.19.31
3 x 3 - ( (-1)^2 - 2)^2
Start evaluating the one in the most inner bracket:
3 x 3 - ( (-1)^2 - 2)^2
= 3 x 3 - (1 - 2)^2
There is one more bracket, so we do what is in the bracket:
3 x 3 - ( (-1)^2 - 2)^2
= 3 x 3 - (1- 2)^2
= 3 x 3 - (-1)^2
= 3 x 3 - 1
Between x and -, we do the x first:
3 x 3 - ( (-1)^2 - 2)^2
= 3 x 3 - (1- 2)^2
= 3 x 3 - (-1)^2
= 3 x 3 - 1
= 9 - 1
Then we do the -:
3 x 3 - ( (-1)^2 - 2)^2
= 3 x 3 - (1- 2)^2
= 3 x 3 - (-1)^2
= 3 x 3 - 1
= 9 - 1
= 8